A measuring method for 3D-analysis of footpositions in figure skating - Drenk, V. (1997)
One of our two camera-pairs recorded the foot area. This pair was connected with a second pair of cameras that was synchronized with the first one and which recorded the usual large format. Using our methods which allows free rotation and zooming of the cameras we were able to develop a special measuring method. The exactness of these points' digitalisation which might be hidden from one camera perspective could be enhanced by inserting the direction information for that point from the other camera into the photogrammetric picture. This procedure to record and process information on complicated jumps was applied during the 1995 European Championship in Dortmund.